Management of Varicella Gangrenosa: A Life-Threatening Condition from Chickenpox - Judith P. M. Schots; Peter Moons; Jan H. M. B. Stoot (Case Reports in Medicine)
Varicella gangrenosa, in which gangrenous ulceration of the skin and/or deeper tissues is seen, is a rare but alarming complication of Varicella infection. An early surgical intervention is generally advised, especially in case of sepsis and/or the presence of large necrotic lesions. We describe a case of a previously healthy 12-month-old boy presenting with sepsis due to Varicella gangrenosa. He presented with moderate lesions of moist gangrene. We treated our patient initially with antibiotics (ceftriaxone and metronidazole) and later on flucloxacillin and antiviral therapy (acyclovir) whereupon his condition rapidly improved and all skin lesions healed entirely. This report highlights the possibility of conservative treatment and emphasizes the significance of acyclovir in the management of chickenpox complicated by moist gangrene due to bacterial superinfection.